Synchrony in the phenologies of fine roots and leaves of Vitellaria paradoxa in different land uses of Burkina Faso - Bazie, Paulin; Ky-Dembele, Catherine; Jourdan, Christophe; Roupsard, Olivier; Zombre, Gerard; Bayala, Jules (Springer Science + Business Media B.V, 2017)
This study focused on leaf and root density dynamics of the most dominant tree species (Vitellaria paradoxa) of West African savannas in two land use types (farmed land and forest). Ten trees located at least 100 m from each other were selected, with five trees each located in the field and in the forest. Five of the trees were of small-diameter [two in the fields (diameter at breast height or DBH 20.1–20.7 cm) and three in the forest (DBH 7.0–8.0–10.8 cm)] and five others were of large-diameter [three in the fields (DBH 38.2–81.8–81.9 cm) and two in the forest (DBH 20.1–20.7 cm)]. One near-vertical rhizotron was installed under each tree to evaluate root density while canopy openness, diffuse and directly transmitted light were monitored by taking hemispheric photograph monthly. After a two-year period of monitoring, the results revealed a strong seasonality in root density with peak root density observed during the rainy season in August and the lowest production during the dry season in April. Significant lowest canopy openness was observed from August to September while the highest occurred from March to May, which was found to be synchronous with fine root dynamics. The light interception followed the same trends as the leaf production. Furthermore, both mature and young trees showed significant higher root density in the fields compared to the forest while the mean values of all the parameters of canopy openness and light transmittance were higher in the forest than the fields.
In Burkina Faso, as well as in other Sahelian countries,parklands constitute the main rural land use system that allows farmers to produce annual crops incombination with multi-purpose trees.
Keywords: Canopy openness; Ecosystem; Hemispherical photography; Savanna; Shea